Studies on the application of Nisin to inoculated packs of canned coconut milk - Narvaiz, Lorna C.
The application of nisin to inoculated packs of canned coconut milk was evaluated. the first phase determined the level of nisin sufficient to destroy spores of Bacillus stearothermophilus while the second phase established the tim-temperature combination which improved the stability of canned coconut milk added with nisin. Canned coconut milk samples added with 50 ppm nisin and processed at 230°F for 45 minutes gave a 99.96% destruction of the inoculated spores of the test organism. Although a complet destruction of the inoculated spores has been found using 100 ppm nisin, canned samples with 50 ppm nisin produced a product which had no significant change in pH and viscosity values. Despite the relative stability of the physico-chemical properties of the canned product using 50 ppm nisin, at heating temperature of 230°F for 40 minutes or less, the commercial sterility of the product was found to be doubtful.